Democracy’s College: The American Community College in the 21st Century: Framing the Issue - Topper, Amelia Marcetti; Powers, Jeanne M. (Education Policy Analysis Archives, 2013)
In this manuscript, the guest editors of the EPAA Special Issue on “Democracy’s College: The American Community College in the 21st Century”: a) introduce the background, history, and context of community colleges in the larger higher education landscape; b) summarize the three research papers and two video commentaries that were peer-reviewed and selected for inclusion in this special issue; and, c) discuss the individual contributions and major themes across the selected papers. Their importance is discussed in terms of each paper’s insights for the general research on this topic and each paper’s potential to inform community college research, practice, and policy.